Revisiting indication for hysterectomy according to PALM-COEIN classification and its correlation with histopathological examination reports - Shanmukhi, Vazeer Bhavya; Vijaya Sree, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hysterectomy is most common major gynaecological surgery. AUB is commonest indication for hysterectomy. Hysterectomy is done when medical/minimally invasive treatment methods fail. It provides permanent relief of symptoms and patient satisfaction. Aim of this study was to correlate the clinical preoperative diagnosis and histopathological findings of cases which needed abdominal hysterectomy. Methods: This prospective study was conducted in Department of OBG at Mamata general hospital, Khammam, during December 2020 to December 2022. The patients were diagnosed based on history, clinical examination and ultrasonography reports. Patients with frank malignancies and uterine prolapse were excluded. Hysterectomy was done wherever it is indicated and the specimens were sent for histopathological examination (HPE). HPE reports were correlated with preoperative indication for hysterectomy. Results: In this study 50 patients who underwent abdominal hysterectomy were studied. Data was recorded in terms of demographics, clinical features, indications of the hysterectomy and histopathological findings. It was observed that, most common clinical diagnosis was leiomyoma [21 women (42%)]. Among these 21 women, histopathological findings of 4 women were different (adenomyosis in 2 cases and unremarkable myometrium in 2 cases). Leiomyoma in myometrium, chronic papillary endocervicitis in cervix, hydrosalpinx in fallopian tubes and simple serous cysts in ovaries were the commonest histopathology noted. Conclusions: Hysterectomy is most widely performed major gynaecological operation and histopathology is mandatory for confirming diagnosis and management. With the improvement in the different treatment options for AUB, hysterectomy in benign disease should only be done when all the other conservative options fail.